Si-Photonics-Based Layer-to-Layer Coupler Toward 3D Optical Interconnection - Nishiyama, Nobuhiko; Kang, JoonHyun; Kuno, Yuki; Itoh, Kazuto; Atsumi, Yuki; Amemiya, Tomohiro; Arai, Shigehisa (IEICE-INST ELECTRONICS INFORMATION COMMUNICATIONS ENG, 2018)
To realize three-dimensional (3D) optical interconnection on large-scale integration (LSI) circuits, layer-to-layer couplers based on Si-photonics platform were reviewed. In terms of optical cross talk, more than 1 mu m layer distance is required for 3D interconnection. To meet this requirement for the layer-to-layer optical coupler, we proposed two types of couplers: a pair of grating couplers with metal minors for multi-layer distance coupling and taper-type directional couplers for neighboring layer distance coupling. Both structures produced a high coupling efficiency with relatively compact (similar to 100 mu m) device sizes with a complementary metal oxide semiconductor (CMOS) compatible fabrication process.